Tourism demand in Malaysia: a panel data analysis of 17 OECD countries / Ravikumar Suppiah and Doris Padmini Selvaratnam - Suppiah, Ravikumar; Selvaratnam, Doris Padmini (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2020)
Tourism is a large contributor to the growth of the Malaysian economy. The natural and built environment, coupled with the diverse local culture, makes Malaysia a unique attraction for foreigners. This paper investigates the main determinants of tourism demand in Malaysia across 17 OECD countries using secondary data and a panel data analysis. Considering the fixed effect (FE) and random effect (RE) models, the Hausman test indicates that the FE model fits the best. This study's relative price is statistically significant with a negative sign, meaning that tourist demand increases when the comparable prices fall; meanwhile, cross-elasticities show substitution effects between Malaysia and alternative destinations. The Visit Malaysia Year campaign in 2014 had positively impacted the tourism demand. The main conclusion drawn is that Malaysian tourism is sensitive to prices. The tourism industry stakeholders need to ensure that tourism services are competitively low through innovative travel packages and offerings. Policymakers may be instrumental in providing a more conducive environment, especially tax exemption and other infrastructure incentives.